Akulturasi Budaya Tionghoa dalam Fungsi dan Makna Koin Kepeng di Bali - Lael, Gracelynn Talitha; Susanti, Elizabeth (UNIVERSITAS INDO GLOBAL MANDIRI, 2025)
Acculturation is a significant phenomenon in cultural development that occurs when two or more cultures interact and influence each other. One enduring example of acculturation in Bali is the use of kepeng coins, locally known as Pis Bolong, which originally functioned as a medium of exchange in traditional economic systems. Over time, kepeng coins underwent a substantial transformation, particularly serving as ritual instruments in Hindu religious ceremonies. The urgency of this study lies in the decreasing availability of kepeng coins in the modern era and their gradual replacement by the rupiah, which risks weakening future generations’ understanding of this cultural symbol. To address this issue, the research employed a literature study method by reviewing relevant books, academic journals, and visual documents. The objective of the study is to analyze the functional changes, symbolic meanings, and Chinese cultural visual elements preserved in kepeng coins. The findings reveal that kepeng coins have served multiple purposes, ranging from currency and markers of social status to offerings in rituals such as melasti, ngaben, and piodalan, as well as materials for crafts with both aesthetic and economic value. Visual elements such as the square hole and Chinese inscriptions symbolize cosmological concepts of earth and heaven, which were reinterpreted within Balinese Hindu traditions. In conclusion, this study emphasizes that kepeng coins represent Sino-Balinese acculturation, reflecting cultural resilience while contributing to the preservation of Balinese identity in the face of modernization.